2020
DOI: 10.1021/acsami.0c00283
|View full text |Cite
|
Sign up to set email alerts
|

Dual Photoluminescence Emission Carbon Dots for Ratiometric Fluorescent GSH Sensing and Cancer Cell Recognition

Abstract: We developed a facile strategy for the fabrication of dual-emission carbon nanodots (CDs) and demonstrated their applications for ratiometric glutathione (GSH) sensing and for differentiating cancer cells from normal cells. Dual-emission CDs were synthesized using a simple hydrothermal treatment of alizarin carmine as the carbon source, manifesting intriguing dual-emission behavior at 430 and 642 nm. With increasing GSH concentration, the fluorescence band at 430 nm increased gradually, whereas that at 642 nm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(70 citation statements)
references
References 42 publications
0
67
0
1
Order By: Relevance
“…In a related study, [57] multilayered π-conjugated cores of red emissive CDs were exfoliated into single-to-few-layer CDs by microwave heating, which facilitated stronger interaction of DMF molecules with outer layers of CDs, leading to the appearance of the absorption band at 724 nm and PL band at 770 nm. Li and coworkers reported on small (2 nm) spherical CDs with dual emission at 430 and 642 nm, [98] where in presence of glutathione, the long-wavelength emission of CDs was efficiently quenched due to the glutathione-induced aggregation, but blue emission remained. It was concluded that the red emissive centers were situated nearby the CD surface.…”
Section: Steady-state Photoluminescencementioning
confidence: 99%
“…In a related study, [57] multilayered π-conjugated cores of red emissive CDs were exfoliated into single-to-few-layer CDs by microwave heating, which facilitated stronger interaction of DMF molecules with outer layers of CDs, leading to the appearance of the absorption band at 724 nm and PL band at 770 nm. Li and coworkers reported on small (2 nm) spherical CDs with dual emission at 430 and 642 nm, [98] where in presence of glutathione, the long-wavelength emission of CDs was efficiently quenched due to the glutathione-induced aggregation, but blue emission remained. It was concluded that the red emissive centers were situated nearby the CD surface.…”
Section: Steady-state Photoluminescencementioning
confidence: 99%
“…And the two peaks at 531.5 and 532.7 eV in the high-resolution O1s spectrum (Fig. 2C) belonged to the C=O/C-OH, and C-O-C groups, 21,22 respectively. The N1s band can be divided into three peaks at 399.8, 400.6, and 401.5 eV, which indicates the existence of C=N, C-N, and -NH2 groups, 19,20 respectively.…”
Section: Characterization and Optical Properties Of The Nfncbsmentioning
confidence: 96%
“…Cancer has become an emerging health issue in the world. [1][2][3][4] Recently, imaging-guided stimuli-responsive nanoscale drug delivery system for cancer therapy has attracted considerable attention and become one of the research hotspots in targeted cancer therapy. [5][6][7][8][9] In general, ideal multifunctional drug delivery system for targeted therapy of cancer through intravenous administration will rstly circulate in the blood, then accumulate at tumor sites and nally release the drugs aer internalization into cancer cells.…”
Section: Introductionmentioning
confidence: 99%